2013
DOI: 10.1007/s11262-012-0869-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of betanodaviruses isolated from sea bass and sea bream cultured along the Tunisian coasts

Abstract: Viral nervous necrosis (VNN) is a serious viral disease affecting farmed sea bass (Dicentrarchus labrax). Only scarce molecular data are available on the disease-causing betanodavirus populations in Tunisia. Therefore, we carried out the first molecular survey of betanodaviruses in farmed sea bass and sea bream (Sparus aurata) along the Tunisian coasts. Among 81 samples from five farms, 20 tested positive with RT-PCR, not only in clinical cases but also in asymptomatic fish before and during outbreaks. Positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Comparison of a partial sequence from the coat protein gene of the wild isolates showed a similarity ranging from 94% to 97% to the Tunisian nodaviruses retrieved from farmed sea bass and sea bream [4,24]. In addition, the similarity with the rest of the genotypes was ranging from 88% to 97% (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Comparison of a partial sequence from the coat protein gene of the wild isolates showed a similarity ranging from 94% to 97% to the Tunisian nodaviruses retrieved from farmed sea bass and sea bream [4,24]. In addition, the similarity with the rest of the genotypes was ranging from 88% to 97% (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…The evolutionary distances were computed using the Kimura 2-parameter method [26] and are in the units of the number of base substitutions per site [27][28][29][30]. GenBank accession numbers and references for nucleotide sequences are as follow: EU826138.1 [31], EF617326 [32], NC_013461 [33], KF386164 [34], KY354698.1 [35], GU826692.1 [36], HE796793.1 [37], KY354694.1 [35], HE796789.1 [37], HE796797.1 [37], HE796788.1 [37], HE796791.1 [37], HE796790.1 [37], HE796785.1 [37], HE796798.1 [37], HE796799.1 [37], HE796794.1 [37], HE796786.1 [37], AJ698093.1 [38], AF318942.1 [39], AF499774.1 [40], HE796795.1 [37], HE796796.1 [37], HE796787.1 [37], HE796784 [37], KM588181.1 [41], KP455642.1 [42], AY284968.1 [43], HE796792.1 [37], JN190021.1 [44].…”
Section: Resultsmentioning
confidence: 99%
“…When used in conventional PCR, the oPVP154-155 primer set proved to be useful alone to detect RGNNV isolates during an epidemiological study in sea bass and sea bream in Tunisian farms (Haddad-Boubaker et al, 2013). A Taqman probe was therefore added to the method to increase specificity in an attempt to extend the method to the widest possible panel of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…It is rapid, sensitive, specific and has a potential for being used routinely in different geographic regions and host species with a very high chance of detecting any isolate. An additional advantage of the targeted region is its potential, after sequencing, for providing a rough genotyping in order to identify the viral species (Haddad-Boubaker et al, 2013). In addition, the region targeted by the Taqman probe is subjected to rare variations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this species has often been reared in close vicinity to sea bass in areas where VNN is endemic. Interestingly, most of the VNN outbreaks in seabass were associated to the RGNNV species202122, which suggested that maybe sea bream was not susceptible to this specific virus species. This finding was supported also under experimental conditions.…”
mentioning
confidence: 99%